First aid for the emergency medicine clerkship - Stead, Latha G. (McGraw-Hill Medical, 2011)
"The emergency medicine clerkship survival guide in the super-effective First Aid format Written by students who just completed their clerkship First Aid for the Emergency Medicine Clerkship is a comprehensive high-yield review based on the clerkship's core competencies. Written by students who just completed their clerkship and reviewed by faculty to ensure relevance and accuracy, the book covers everything students must know to do well in the ED and ace the emergency medicine shelf exam. New features include mini-cases integrated throughout to give a clinical "face" to disease discussions and 8 pages of full color images. Features Hundreds of frequently tested high-yield facts from emergency medicine in-service exams, shelf exams, and the USMLE Step 2 give you the edge on exam day Mnemonics, diagrams, and illustrations help you recall must-know concepts Insider tips for outstanding performance from students who excelled Ward Tips arm you with answers to common "pimp" questions Classifieds direct you to high-yield websites, scholarships, and extracurricular activities and publishing opportunities Typical Scenario and Exam Tip study boxes prepare you for exam questions NEW mini-cases highlight classic patient presentations and frequently tested cases The content you need to excel on the clerkship: Section I: How to Succeed in the EM Clerkship; Section II: High-Yield Facts; Resuscitation; Diagnostics; Trauma; Neurologic Emergencies; Head and Neck Emergencies; Respiratory Emergencies; Cardiovascular Emergencies; GI Emergencies; Renal and GU Emergencies; Hematologic and Oncologic Emergencies; Gynecologic Emergencies; OB Emergencies; Musculoskeletal Emergencies; Endocrine Emergencies; Dermatologic Emergencies; Procedures; Emergency Toxicology; Environmental Emergencies; Ethics, Medico-legal Issues, and EBM; Section III: Classified"--Provided by publisher